What makes the Technology Strategic Decision Making More Well- organized? - Ahmad, Sayad Fayaz; Alasmari, Talal M. (The journal of contemporary issues in business and government, 2021)
The study aims to find out the factors which have a strong impact on technology-related decisions making. After a deep literature review, various factors that have a great influence on decision making were found out. These are experience, intelligence, information availability, and organizational capabilities. The research is based on a review of literature related to the subject and its analysis. It recommends that for making strategically suitable decisions, the decision-makers should have attributes like individual experience, intelligence, and availability of information and capabilities of the organizations to make suitable decisions. The study adds a much clear picture of the elements and their association with technology decision making. And can be used for the development of a decision- making model for any technology industry during high uncertainty.